Central Banking in Rawls's Property-Owning Democracy. (October 2019) - van 't Klooster, Jens
The dramatic events of the crisis have reignited debates on the independence of central banks and the scope of their mandates. In this article, I contribute to the normative understanding of these developments by discussing John Rawls's position in debates of the 1950s and 1960s on the independence of the US Federal Reserve. Rawls's account of the central bank in his property-owning democracy, Democratic Central Banking (DCB), assigns authority over monetary policy directly to the government and prioritizes low unemployment over price stability. I contrast DCB with Central Bank Independence (CBI), which requires that the central bank is independent of the government and pursues low inflation. I evaluate DCB by asking whether justice as fairness requires democratic control of the central bank and argue that it does not. Instead, so I argue, the choice between DCB and CBI should be justified in terms of the difference principle. By reflecting on central banking in a property-owning democracy, I cast new light on the Rawlsian realistic utopia of a just capitalist society, while also investigating democratic objections to today's independent central banks.